A DECISION MODEL FOR PHARMACEUTICAL MARKETING AND A CASE STUDY IN TURKEY - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
The choice of the appropriate product for the portfolio of a pharmaceutical company in terms of its strategy and long term commercial value is a sophisticated multi-criteria decision problem in pharma economics. This paper provides a systematic method for licensing in pharma industry and proposes a Fuzzy AHP based decision model for the decision makers in pharmaceutical industry to assess potentials of different products for license-in that may be proper for their portfolio. An application of the proposed model is also performed for a pharmaceutical company in Turkey.
Keywords: Marketing; Decision making; Pharma industry; ANALYTIC HIERARCHY PROCESS; SUPPORT-SYSTEM; FUZZY AHP; SELECTION